The notion of State aid and regulation in the EU: drawing the shape of a moving target - Piernas López, Juan Jorge (CUADERNOS DE DERECHO TRANSNACIONAL, 2010)
This paper deals with the notion of economic activity in European State aid law. The notion of economic activity defines the scope of application of several Treaty provi-sions. In this regard, the competition rules, the freedom to provide services, the right of estab-lishment, and the free movement of workers only apply in the ambit of economic activities. However, there is not one but several tests in the case law of the Court of Justice of the Euro-pean Union to define what an economic activity is. This paper aims to suggest which test should be applied to State aids in light of the particular nature of this area of EU law, between a competition and free movement logic. For that purpose, the paper first examines the notion of economic activity in relation to the competition and free movement provisions of the Treaty. Second, it analyzes in more detail the notion of economic activity in the field of State aid in light of the European Commission practice. Finally, the paper draws some conclusions from the above and proposes a functional, not material, interpretation of economic activity for State aid law.
Keywords: Economic activity; undertaking; notion of state aids; state aids; Competition Law